1997
DOI: 10.2527/1997.752437x
|View full text |Cite
|
Sign up to set email alerts
|

Development of digestive enzymes in pigs with emphasis on lipolytic activity in the stomach and pancreas.

Abstract: The effect of age and weaning on the activities of digestive enzymes with emphasis on the lipolytic enzymes before and after weaning was investigated. The activities of amylase, chymotrypsin, trypsin, carboxyl ester hydrolase, pancreatic lipase, and colipase in pancreatic tissue and the activity of gastric lipase in the cardiac mucosa of the stomach in 45 pigs were response variables. The activity of trypsin was not affected by weaning and the rate of increase was similar during the whole experiment. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
6
82
1
5
Order By: Relevance
“…However, FFA constituted the major lipid fraction in feces for all treatments, suggesting that the absorption of FFA is the main limiting factor of fat absorption in weaning piglets. Several authors have attributed the decreased fat apparent absorption in the post-weaning period to insufficient secretion of bile (Jones et al, 1992), although others have also suggested a decreased secretion of lipases due to the adaptation of the pancreas to the new diet (Lindemann et al, 1986;Jensen et al, 1997).…”
Section: Digestibility Balancementioning
confidence: 99%
“…However, FFA constituted the major lipid fraction in feces for all treatments, suggesting that the absorption of FFA is the main limiting factor of fat absorption in weaning piglets. Several authors have attributed the decreased fat apparent absorption in the post-weaning period to insufficient secretion of bile (Jones et al, 1992), although others have also suggested a decreased secretion of lipases due to the adaptation of the pancreas to the new diet (Lindemann et al, 1986;Jensen et al, 1997).…”
Section: Digestibility Balancementioning
confidence: 99%
“…In addition, the fat is emulsified and it can be more easily digested in this form. Piglets lose this nutrition source at the moment of weaning and it is a question how to substitute it adequately (Jensen et al, 1997). Heugten and Odle (2000) considered insufficient digestibility to be the major problem of adding fats into feed mixtures for piglets.…”
mentioning
confidence: 99%
“…O aumento crescente na atividade da amilase, à medida que o leitão ganha peso, pode ser explicado pela necessidade do animal em hidrolisar grandes quantidades de amido. Este resultado concorda com o obtido por JENSEN et al (1997), que verificaram incremento linear da amilase natural em relação ao peso vivo do animal.…”
Section: Resultsunclassified